Multiplicação de distribuições no estudo de soluções de ondas delta choque - Ferreira, Liliane da Cunha (Universidade Federal de São Carlos, 2023)
In this work, we will find the delta shock wave solution for three Riemann problem where two are hyperbolic systems of conservation laws with linear damping and a three-component nonlinear chromatography model. We will apply concept of α-solutions to find them. This concept uses the product of distributions.
Multiplication of distributions in the study of delta shock wave solutions
Keywords: Amortecimento linear; Cromatografia; Onda delta choque; Problema de Riemann; Produto de distribuições; Sistema não estritamente hiperbólico; Linear damping; Chromatography; Delta shock wave; Riemann problem; Product of distributions; Non-strictly hyperbolic system; CIENCIAS EXATAS E DA TERRA::MATEMATICA